Needs Analysis of Early Childhood Education Teachers Regarding the Integration of Acehnese Heroic Values in Character Education - Elfiadi Elfiadi; Panggung Sutapa; Nur Hayati; Anisaturrahmi Anisaturrahmi (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
Patriotism in early childhood is a key foundation for social cohesion and national identity. However, integrating local cultural values into character education remains a challenge in many early childhood settings. This study explores early childhood education teachers’ needs for integrating Acehnese heroic values into character learning. A mixed-methods sequential explanatory design was employed, involving a survey of 86 kindergarten teachers in North Aceh, followed by focus group discussions (FGD) and in-depth interviews. The findings revealed three main themes: (1) learning practices were largely dominated by conventional approaches, with limited use of Acehnese heroic narratives; (2) teachers faced challenges related to inadequate training in contextual pedagogy, limited learning resources, and difficulties in designing meaningful learning activities; and (3) most teachers expressed a strong need for innovative learning models grounded in local wisdom, active child participation, and practical teaching guidelines. The study identifies three key areas of need: content, pedagogy, and system support. Its main contribution lies in linking teachers’ needs analysis with local heroic values as a foundation for integrating character education into early childhood learning.